Accommodating business travellers: The organisation and spaces of serviced apartments in Cape Town, South Africa - Greenberg, Desire; Rogerson, Jayn M. (Bulletin of Geography. Socio-economic Series, 2018)
In recent years several new forms of lodging have developed as alternatives to the hotel. For business travellers the serviced apartment has emerged as a new phenomenon. Within extant accommodation scholarship the service apartment sector has attracted minimal international attention either from tourism or property researchers. This paper analyses the development and character of service apartments in one of South Africa’s major business tourism destinations, the city of Cape Town. It is disclosed that serviced apartments are clustered around different business nodes in the city and spatially differentiated in terms of serving distinctive business traveller markets.